2012
DOI: 10.1186/1756-3305-5-192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of topically administered imidacloprid + pyriproxyfen and orally administered spinosad against cat fleas (Ctenocephalides felis): Impact of treated dogs on flea life stages in a simulated home environment

Abstract: BackgroundCat fleas, Ctenocephalides felis, are one of the most common ectoparasites infesting dogs and their environments. This study evaluated the efficacy of imidacloprid + pyriproxyfen (PPF) (Advantage® II for Dogs) and spinosad (Comfortis®) against established C. felis populations in dogs’ simulated home environments.MethodsThirty Beagle dogs were randomly assigned to three groups of 10 dogs each and treated twice (Study Days 0 and 28) with imidacloprid + PPF, spinosad tablets, or a negative control (untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The high percent efficacy of spinosad for the treatment and prevention of flea infestations (>98 % and >99 % using arithmetic and geometric means, respectively) is comparable to the efficacy of this molecule that has been reported in most studies where dogs were experimentally infested by C. canis [ 10 ] or C. felis [ 5 , 6 , 9 , 19 ], as well as after experimental infestation with C. felis of dogs in a home simulated environment [ 13 ]. Also, the reduction of flea counts witnessed in the present study was very similar to those reported previously in field trials of spinosad [ 5 , 14 , 15 ], spinosad-milbemycin oxime combination [ 20 ] and spinosad in combination with an amitraz collar [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The high percent efficacy of spinosad for the treatment and prevention of flea infestations (>98 % and >99 % using arithmetic and geometric means, respectively) is comparable to the efficacy of this molecule that has been reported in most studies where dogs were experimentally infested by C. canis [ 10 ] or C. felis [ 5 , 6 , 9 , 19 ], as well as after experimental infestation with C. felis of dogs in a home simulated environment [ 13 ]. Also, the reduction of flea counts witnessed in the present study was very similar to those reported previously in field trials of spinosad [ 5 , 14 , 15 ], spinosad-milbemycin oxime combination [ 20 ] and spinosad in combination with an amitraz collar [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…However, the increased relative abundance of C. canis in sheep at days 28 and 84 does not seem to be in favor of this explanation. The fast adult flea killing activity of spinosad has a strong negative impact on egg production so that new adult flea emergence progressively declines when all dogs (and obviously other possible hosts) are treated [ 9 , 12 , 13 ]. In our study, administration of spinosad in some of the dogs in each farm may have reduced the relative abundance of C. canis , which was the predominant flea species at day 0, thus leading to an increased relative abundance of P. irritans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of imidacloprid and moxidectin (Advantage Multi®, Advocate®) is used for prevention of heartworm disease [ 16 ] and for treatment of fleas, intestinal nematodes [ 17 ], sarcoptic mange [ 18 ], demodex mange [ 19 ] and ear mites [ 20 ]. Imidacloprid combined with pyriproxyfen (Advantage II®) extended the activity against all life stages of fleas [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works mentioned that LC 50 (84 Nano-gram/L) of imidacloprid to larvae of Aedes aegypti. Uragayala et al evaluated the Larvicidal effect of neonicotinoid insecticides against susceptible and resistant mosquito's strains [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: Compoundsmentioning
confidence: 99%